Structure and Electrical Properties of Carbon-Rich Polymer Derived Silicon Carbonitride (SiCN) - Oluwole Daniel Adigun; Emmanuel Ricohermoso; Ayodele Abeeb Daniyan; Lasisi Ejibunu Umoru; Emanuel Ionescu (Ceramics, 2022)
This article reports on the structure and electronic properties of carbon-rich polysilazane polymer-derived silicon carbonitride (C/SiCN) corresponding to pyrolysis temperatures between 1100 and 1600 °C in an argon atmosphere. Raman spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), Scanning Electron Microscopy (SEM) and Hall measurements were used to support the structural and electronic properties characterization of the prepared C/SiCN nanocomposites. A structural analysis using Raman spectroscopy showed the evolution of sp2 hybridized carbon phase that resulted from the growth in the lateral crystallite size (La), average continuous graphene length including tortuosity (Leq) and inter-defects distance (LD) with an increase in pyrolysis temperature. The prepared C/SiCN monoliths showed a record high room temperature (RT) electrical conductivity of 9.6 S/cm for the sample prepared at 1600 °C. The electronic properties of the nanocomposites determined using Hall measurement revealed an anomalous change in the predominant charge carriers from n-type in the samples pyrolyzed at 1100 °C to predominantly p-type in the samples prepared at 1400 and 1600 °C. According to this outcome, tailor-made carbon-rich SiCN polymer-derived ceramics could be developed to produce n-type and p-type semiconductors for development of the next generation of electronic systems for applications in extreme temperature environments.